Facile fabrication of hydrophobic surfaces on mechanically alloyed-Mg/HA/TiO2/MgO bionanocomposites - Khalajabadi, Shahrouz Zamani (Elsevier, 2015)
The effect of mechanical alloying and post-annealing on the phase evolution, microstructure, wettability and thermal stability of Mg-HA-TiO2-MgO composites was investigated in this study. Phase evolution and microstructure analysis were performed using X-ray diffraction, field-emission scanning electron microscopy, transmission electron microscopy and atomic force microscopy, as well as the wettability determined by contact angle measurements with SBF. The 16-h mechanical alloying resulted in the formation of MgTiO3, CaTiO3, Mg3(PO4)2 and Mg(OH)2 phases and a decrease in wettability of the nanocomposites. A hydrophobic film with hierarchical structures comprising nanoflakes of MgTiO3, nano-cuboids of CaTiO3, microspheres of Mg3(PO4)2 and Mg(OH)2 was successfully constructed on the surface of the Mg-based nanocomposites substrates as a result of the post-annealing process. After 1-h annealing at 630 °C, the synthesized hydrophobic surface on the nanocomposite substrates decreased the wettability, as the 8-h-mechanically alloyed samples exhibited a contact angle close to 93°. The formation activation energies and reaction kinetics of the powder mixture were investigated using differential thermal analysis and thermal gravimetric analysis. The released heat, weight loss percentage and reaction kinetics increased, while the formation activation energies of the exothermic reactions decreased following an increase in the milling time